Sexuality of women with cervix cancer after treatment: literature review - Nur Afni Sharfina; Ratna Indriawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: Cervical cancer is a complex disease that requires comprehensive treatment from clinical professionals. Treatment of women with cervical cancer, such as radiation, chemotherapy and also surgery (hysterectomy). The positive effect of treatment is that it kills cancer cells. There were also physically negative treatments offered (chemotherapy and radiation), such as vaginal dryness, redness of the vaginal area and vaginal canal. Purpose: This adjustments are linked to sexual function directly. The main objective of this literature review is to finding clinical reports on the sexuality of cervical cancer patients undergoing cervical cancer treatment. This study is a literature review. Data based used are NCBI and Google Schoolar. Methods: This research is a study of literature. NCBI and Google Schoolar are used based on results. The writer uses keywords  "sexuality, cancer, after treatment, cervix".  Inclusion criteria for papers were released in 2016-2020, the analysis approach was quantitative, papers were written in English, information on the subject was found in publications.Results:  12 articles that fulfilled the inclusion criteria were analyzed and the results of this literature. Conclusion:It can be suggested, after analyzing it, that cancer therapy given to cervical cancer patients can influence sexuality, especially sexual function. The treatment available (radiotherapy, chemotherapy, and the surgical process) has a significant effect on the female reproductive organs.